Development Policy and Multilateralism after COVID-19 - United Nations (United Nations, 2020)
This Policy Note assembles analysis by members of the UN Committee for Development Policy and their co-authors on different angles of the COVID-19 (coronavirus) crisis and the challenges and opportunities it presents for development policy and multilateralism. The document addresses, among other issues: new ways of designing the relationship between governments and private actors that puts public interest at the center; principles and concrete ideas for a multilateral response to COVID-19 as well as for a new multilateralism going forward; and how to respond to COVID-19 in a context of severe inequalities, including gender-based inequalities.